Is It Worth It? On the Returns to Holding Political Office - Heléne Berg (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper estimate causal effects of being elected in a local election on monetary returns. The claim for causality can be made thanks to a research design where the income of some candidate who just barely won a seat is compared to that of some other candidate who was close to winning a seat for the same party, but ultimately did not. The design is made possible thanks to comprehensive data covering all political candidates in the period 19912006. I establish that monetary returns are absent both in the short and long run. Instead, politicians seem to be motivated by non-monetary returns, and I show that being elected locally once can be an effective starting point for enjoying such payoffs.
Keywords: C23; D72; J44; 330; returns to politics; incumbency effects; regression discontinuity design